2018
DOI: 10.1002/batt.201800047
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Room Temperature Liquid Metals for Mechanically Robust Silicon Anodes in Lithium‐Ion Batteries

Abstract: Silicon has attracted attention as one of the most promising anode materials for future generation energy storage devices, owing to its high theoretical specific capacity. However, its use has been impeded by significant volume expansion during electrochemical lithiation. In this work we utilise liquid galinstan (68.5 % Ga, 21.5 % In and 10 % Sn) to repair the cracking caused by volume expansion in Si thin film and Si composite electrodes. A bridging mechanism is observed, through which the electrical conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Lithiophilic coating is an effective strategy to enhance the wettability between liquefied lithium and carbon matrix, because these coating layers can react with molten lithium to reduce the surface energy of carbon matrix or form alloys with lithium. Silicon can coat on the carbon-based materials via chemical vapor deposition to form the Li x Si alloys (Liang et al, 2016;Hapuarachchi et al, 2018). Thus, the molten metallic lithium can easily and quickly flow into the scaffolds with silicon coating.…”
Section: Carbon-based Materials To Construct Composite Anodesmentioning
confidence: 99%
“…Lithiophilic coating is an effective strategy to enhance the wettability between liquefied lithium and carbon matrix, because these coating layers can react with molten lithium to reduce the surface energy of carbon matrix or form alloys with lithium. Silicon can coat on the carbon-based materials via chemical vapor deposition to form the Li x Si alloys (Liang et al, 2016;Hapuarachchi et al, 2018). Thus, the molten metallic lithium can easily and quickly flow into the scaffolds with silicon coating.…”
Section: Carbon-based Materials To Construct Composite Anodesmentioning
confidence: 99%
“…Exploiting rechargeable battery technologies with enhanced performance as well as low cost and environmental friendliness has become a global and urgent demand since the explosive growth of portable electronic devices, electric vehicles as well as large‐scale energy storage . Meanwhile, the limited and uneven distribution of lithium resource has stimulated extensive investigations of energy storage devices based on other abundant metal ions, such as Na + , K + , Al 3+ ,, etc.…”
Section: Figurementioning
confidence: 99%
“…Consequently, attributed from the hybrid battery design, this SHB exhibits excellent rate capability and cycling performance with a reversible capacity of 80 mAh g À1 at 2 C over a voltage window of 0-3.8 V and capacity retention of 87 % after 1000 cycles at 10 C.Exploiting rechargeable battery technologies with enhanced performance as well as low cost and environmental friendliness has become a global and urgent demand since the explosive growth of portable electronic devices, electric vehicles as well as large-scale energy storage. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Meanwhile, the limited and uneven distribution of lithium resource has stimulated extensive investigations of energy storage devices based on other abundant metal ions, such as Na + , [12][13][14][15][16][17][18][19][20][21][22][23][24][25] K + , [26][27][28][29][30] Al 3 + , [31,32] etc. Among them, sodium-ion batteries (SIBs) have attracted increased attention owing to the merits of low potential (À2.71 V vs. standard hydrogen electrode (SHE)), high natural abundance, low cost, and similar electrochemical properties to lithium.…”
mentioning
confidence: 99%
“…22 Our recent work confirmed the crack healing effect of galinstan in Si anode and the improvement in electrochemical performance. 23 Considering its mobility and electrochemical capacity, we identified that it is worthwhile to explore the possibility of using liquid metal to solve the delamination problem at the active materials/current collector interfaces in Li-ion battery electrodes.…”
mentioning
confidence: 99%
“…Our previous work also confirms the solid nature of liquid metal nanoparticles upon lithiation. 23 During delithiation, as Li + ions move away from the anode, galinstan regains its liquid nature as depicted in Figure S4. This transformation is critical, as cracking in the Si anode generally occurs during delithiation under tension forces, confirmed by our previous experiments and molecular dynamics simulations.…”
mentioning
confidence: 99%